2021
DOI: 10.3390/ejihpe11030079
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 Pandemic on the Mental Health of Working Adults in the Czech Republic: Analysis of Self-Report Psychological Data in a One Year Perspective

Abstract: The article presents research evidence on psychological impacts of the COVID-19 pandemic on the economically active Czech population aged 18–64 (n = 1603; 365 men and 1238 women) within a one year perspective. The aim is to describe the differences in the reported mental health indicators (anxiety, depression, and distress) for women and men in the four age groups, two groups with different working statuses (continuation of work/interrupted working status), and between two phases of the epidemic (March to May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…During the second wave, both groups of parents experienced higher levels of anxiety, stress, and depression, but the prevalence was significantly higher in parents of autistic children. Deterioration in the mental health of adults was similarly reported in neighboring European countries [6][7][8][9][10] and in research focusing on parents of children with ASD [25,26]. Insufficient or unclear information was the most prevalent stressor for both groups of parents in our study, which is fitting to the way pandemic rules were being officially announced and how they changed rapidly and unexpectedly at the time.…”
Section: Second Wavesupporting
confidence: 80%
See 2 more Smart Citations
“…During the second wave, both groups of parents experienced higher levels of anxiety, stress, and depression, but the prevalence was significantly higher in parents of autistic children. Deterioration in the mental health of adults was similarly reported in neighboring European countries [6][7][8][9][10] and in research focusing on parents of children with ASD [25,26]. Insufficient or unclear information was the most prevalent stressor for both groups of parents in our study, which is fitting to the way pandemic rules were being officially announced and how they changed rapidly and unexpectedly at the time.…”
Section: Second Wavesupporting
confidence: 80%
“…The results of our research must be interpreted with regard to its limits, especially that it was a series of three cross-sectional studies as opposed to a longitudinal research, and data were collected online via self-report methods. This also led to the predominance of females in our sample, which could have affected our results, since in other studies [5,6,8] women reported more severe mental health issues during the COVID-19 pandemic. On the other hand, following the development of a situation in the same country over a two years period and three pandemic waves while focusing on the same particular research population is the greatest strength of this study.…”
Section: Third Wavementioning
confidence: 87%
See 1 more Smart Citation
“…As face to face personal contact with peers was limited during the COVID-19 pandemic, the opportunities to cope with stress via verbal expressions to others were modified to online communication that may not be an adequate substitute for real-life, face to face interaction. The limited opportunities of coping with stress in face to face contact could also be one of the factors influencing higher self-reported levels of stress in women compared to men during the outbreak of COVID-19 in CZ, DE, and SK (see also Kučera et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…University teachers at different state universities had many open questions during their self-preparation (see [8,9]): Do I have all the needed technology support? Should I teach in synchronous or asynchronous form?…”
Section: Introduction-different Types Of Universitiesmentioning
confidence: 99%